Heritage properties management in historic centers: subprocesses and main components - Soto, Dariel (2025)
Urban management, as a component of public administration, faces increasing levels of complexity due to the multiplicity of factors influencing territorial development. In this context, the management of heritage properties emerges as a multidisciplinary field that integrates the conservation of cultural heritage with principles of sustainable development and the active participation of local communities. The objective of this research is to identify the key subprocesses and core components involved in the management of heritage properties within historic centers. A descriptive bibliometric study was conducted using the Scopus database, complemented by a qualitative content analysis. Key subprocesses and components in heritage property management were identified through specialized software tools (VOSviewer and UCINET). The study concludes that the management of heritage properties combines the conservation and enhancement of cultural heritage with community participation, through the development of effective strategies that demand shared responsibility and require an integrated, collaborative approach. Its importance can be summarized in three core dimensions: cultural identity, educational value, and economic development.